2019
DOI: 10.21511/ppm.17(2).2019.40
|View full text |Cite
|
Sign up to set email alerts
|

Job enrichment, organizational commitment, and intention to quit: the mediating role of employee engagement

Abstract: In human resource accounting, personnel recruitment cost is an important issue. High turnover of employees triggers this charge. This research focused on the non-financial issue in employee turnovers for various professions. This study examines the effect of job enrichment, a self-development process on the working environment, to the employee’s engagement and organizational commitment, as well as the intention to quit in a different profession. The respondents of this research are 154 workers who have worked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Employees who are satisfied with their career advancement opportunities are therefore more likely to develop a strong emotional attachment or bond with their organisation (Fletcher, 2016;Hirschi, 2018;Meyer & Allen, 1991). Researchers have indicated that organisations that provide career development and mobility opportunities are more likely to positively influence the affective commitment of their employees (Putri & Setianan, 2019;Robbins, 1993;Weng, McElroy, Morrow, & Liu, 2010). It is therefore proposed that satisfaction with career development and advancement opportunities will be positively related to affective commitment of artisans and engineers:…”
Section: Satisfaction With Career Advancement Opportunities and Affective Commitmentmentioning
confidence: 99%
“…Employees who are satisfied with their career advancement opportunities are therefore more likely to develop a strong emotional attachment or bond with their organisation (Fletcher, 2016;Hirschi, 2018;Meyer & Allen, 1991). Researchers have indicated that organisations that provide career development and mobility opportunities are more likely to positively influence the affective commitment of their employees (Putri & Setianan, 2019;Robbins, 1993;Weng, McElroy, Morrow, & Liu, 2010). It is therefore proposed that satisfaction with career development and advancement opportunities will be positively related to affective commitment of artisans and engineers:…”
Section: Satisfaction With Career Advancement Opportunities and Affective Commitmentmentioning
confidence: 99%
“…This certainly agrees with previous research where job enrichment as a form of development has a positive relationship with OCB, and the presence of employee involvement and organizational commitment affects OCB. (Liu et al, 2022;Putri & Setianan, 2019) Good relations from superiors to subordinates to hospitality unit employees foster behavior, employees feel bound to the services the company has provided and many things have been obtained. The higher the supervisor's support mediated by organizational commitment, the OCB will tend to be high, and vice versa, the lower the superior's support mediated by organizational commitment, the OCB will also be low.…”
Section: Discussionmentioning
confidence: 99%
“…The ethical leadership is positively related to organisational commitment (Addai et al, 2019;Aryati et al, 2018), and employee engagement (Sarwar et al, 2020;Zappalà & Toscano, 2020). While organisational commitment is positively related to employee engagement (Adi & Fithriana, 2020;Putri & Setianan, 2019). These earlier studies reflect on direct relationship between ethical leadership and organisational commitment and role of organisational commitment as mediator (Baron & Kenny, 1986).…”
Section: Organisational Commitmentmentioning
confidence: 98%